Wisdom in Song: Analyzing Stoic Metaphors in Imagine Dragons’ Music - Rezky Anshar Trianto Pade; Rusni Podungge; Farid Muhamad (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This research examines the integration of Stoic philosophy and metaphor in the lyrics of Imagine Dragons’ Evolve album, focusing on the songs “Believer,” “Thunder,” and “Whatever It Takes.” Using a qualitative descriptive method within a structuralism framework, this study explores how conceptual metaphors serve as vehicles for conveying Stoic principles such as emotional resilience, self-discipline, and growth through adversity. The analysis reveals that metaphors like “pain,” “chains,” “lightning,” and “sail” are not just stylistic devices, but cognitive structures that articulate key Stoic ideas. For instance, “pain” is portrayed not as suffering to be avoided, but as a catalyst for inner strength and transformation, reflecting the Stoic view that adversity is necessary for personal growth. Similarly, images of “chains” symbolize psychological constraints, while “lightning” and “sail” represent dynamic energy and purposeful direction in life. These metaphors map abstract philosophical concepts onto concrete, emotionally resonant imagery, allowing listeners to engage with complex ideas in an intuitive and relatable manner. The study demonstrates that the figurative language in Imagine Dragons’ lyrics transforms emotional experiences into philosophical reflections, bridging ancient wisdom with contemporary expression. This suggests that popular music, through metaphor, can function as a modern medium for philosophical discourse, particularly for young audiences. In doing so, this research contributes to the broader field of literary and philosophical studies by illustrating how modern song lyrics can reflect and disseminate classical ideas, fostering a deeper appreciation of Stoic values through the lens of popular culture.